Knowledge Management And Job Performance in Higher Education: The Role Of Leadership and Organizational Culture - Sambas Ali Muhidin; Achmad Hufad; Nani Sutarni; Fahmi Jahidah Islamy; Rasto Rasto; Tutik Inayati (AL-ISHLAH: Jurnal Pendidikan, 2022)
Implemented knowledge management (KM) in universities is currently a significant and interesting topic to be discussed since universities’ human resource possess knowledge. Ultimately, knowledge management is essential in order to increase university lecturers’ performance. Knowledge management must be supported by leadership and organization culture that would support each process of KM, which includes knowledge creation, knowledge transfer and utilization of knowledge. This study tested a model that shows the influence between KM, job performance, leadership, and organizational culture. This study collected sample from 150 lecturer respondents in seven universities in Bandung using random sampling. We analyze the variables (leadership, organizational culture, KM, and job performance) from questionnaire using Structured Equation Modelling (SEM). Research results have shown that the relationship between leadership and KM has a positive and significant impact, that the relationship between organizational culture and KM has a positive and significant impact, that leadership and job performance have a positive and significant impact, that organizational culture and job performance have a positive and significant impact, and there is a positive and significant influence between KM and job performance. This study concludes leadership, organizational culture, KM, and job performance in universities in Bandung are included in positive category. There are significant and positive influences on variables analyzed.